Increased Numbers of Culturable Inhibitory Bacterial Taxa May Mitigate the Effects of Batrachochytrium dendrobatidis in Australian Wet Tropics Frogs - Bell, Sara C.; Garland, Stephen; Alford, Ross A. (Frontiers in Microbiology, 2018)
Symbiotic bacterial communities resident on amphibian skin can benefit their hosts. For example, antibiotic production by community members can control the pathogen Batrachochytrium dendrobatidis (Bd) and it is possible for these community members to be used as probiotics to reduce infection levels. In the early 1990s, the emergence of Bd caused declines and disappearances of frogs in the Australian Wet Tropics; the severity of its effects varied among species and sites. Some species have since recolonised despite enzootic Bd within their populations. This variation in history among species and sites provided an opportunity to investigate the role of anti-fungal cutaneous bacteria in protecting frogs against Bd infection. We collected cutaneous swab samples from three species of frogs at two upland and two lowland sites in the Wet Tropics, and used in vitro challenge assays to identify culturable Bd-inhibitory bacterial isolates for further analysis. We sequenced DNA from cultured inhibitory isolates to identify taxa, resulting in the classification of 16 Bd-inhibitory OTUs, and determined whether inhibitory taxa were associated with frog species, site, or intensity of infection. We present preliminary results showing that the upper limit of Bd infection intensity was negatively correlated with number of inhibitory OTUs present per frog indicating that increased numbers of Bd-inhibiting taxa may play a role in reducing the intensity of Bd infections, facilitating frog coexistence with enzootic Bd. One upland site had a significantly lower prevalence of Bd infection, a significantly higher proportion of frogs with one or more culturable Bd-inhibitory OTUs, a greater number of inhibitory bacterial genera present per frog, and statistically significant clustering of individual frogs with similar Bd-inhibitory signatures when compared to all other sites. This suggests that Bd-inhibitory taxa are likely to be particularly important to frogs at this site and may have played a role in their ability to recolonise following population declines. Our findings suggest that the use of multi-taxon Bd-inhibitory probiotics to support at-risk amphibian populations may be more effective than single-taxon alternatives.